Determining the difference of kick tolerance with single bubble and dynamic multiphase models: Evaluation of well-control with water/synthetic based muds - Khan, J.A. (Ain Shams University, 2022)
Determining the magnitude of an influx into the wellbore when a kick event occurs is very important during well design as well as the well execution phases. This research is conducted to determine the kick tolerance where the single bubble phase model is applied and also to compare it with the dynamic multiphase model. The information on the well and the parameters used are taken from the high pressure and high temperature well drilled in Malaysia. Dynamic multiphase modelling is capable of supporting more kick volume compared to single bubble gas phase modelling where it considers multiple fluid phase in an influx and applies the gas characteristic to have a multiphase pressure loss. Dynamic multiphase gives more kick tolerance to fracture the weakest point at the casing shoe where single bubble gas phase is more conservative when it allows influx. The effect of pore pressure, mud weight, mud type, oil composition in mud, as well as the circulation kill rate are explored in dynamic multiphase. Increasing the mud weight in either case reduces the maximum allowable kick volume of an influx due to the reduction in MAASP between fracture pressure and hydrostatic pressure at the casing shoe. Higher kick volume can be achieved using WBM compared to SBM. In addition, a sensitivity analysis is performed from the dynamic multiphase simulations to analyze the impact on the kick tolerance during the increase in mud weight as well as the pore pressure uncertainties. Moreover, the impact of kick tolerance has been investigated when different types of mud are used, such as water-based mud and synthetic-based mud. Based on the accuracy of the presented procedure, the prediction of kick tolerance from dynamic multiphase modelling can be used as a guideline to identify the behavior of an influx when a kick event occurs. Â© 2022 THE AUTHORS